DYNAMIC ANALYSIS OF REDUCTIONS IN PUBLIC DEBT IN AN ENDOGENOUS GROWTH MODEL WITH PUBLIC CAPITAL. (9th September 2016) - Maebayashi, Noritaka; Hori, Takeo; Futagami, Koichi
Abstract : We construct an endogenous growth model that includes productive public capital and government debt. We assume that the government debt-to-GDP ratio is gradually adjusted to a target level, reflecting the permanent commitment rules in the Stability and Growth Pact or the Maastricht Treaty in the European Union (i.e., the well-known 60% rule). These rules affect government borrowing and public investment. Here, we examine the welfare implications of the permanent commitment rules. We find that fiscal consolidation based on the rules improves social welfare. Moreover, the improvement in welfare accelerates as fiscal consolidation progresses more rapidly. Last, we also discuss and derive the optimal long-run debt-to-GDP ratio.